Hubungan antara intensitas Pruritus Nokturna dengan Kualitas Tidur pada Penderita Skabies - Ghani Silahudin; Erma Sulistyaningsih; Heni Fatmawati (Faculty of Medicine, Universitas Andalas, 2021)
Objective: To analyze the relationship between the intensity of nocturnal pruritus and the sleep quality of scabies patients. Method: This was an analytic study with cross-sectional design. The subject was recruited by total sampling. Data was analysed using the Spearman correlation test. Result: As many as 160 out of 302 students (53%) were suffering from scabies. Majority of patients were 13 years old, at the 7th grade of school, had a normal Body Mass Index (BMI), had an onset of scabies ≤ 3 months and not in the scabies treatment period in the last 1 month. There were 22 scabies patients matched the inclusion and exclusion criteria. As many as 5 out of 22 patients had mild nocturnal pruritus,10 patients had moderate nocturnal pruritus and 7 patients had severe nocturnal pruritus. There were 13.6% had good sleep quality and 86.4% had poor sleep quality. Analysis using Spearman test showed the value of p=0.65 implicated that there was no significant correlation between the intensity of nocturnal pruritus and the sleep quality of scabies patients. Conclusion: There was no relationship between the intensity of nocturnal pruritus and the sleep quality of scabies patients at the Pesantren male dormitory.